Mineralogical Characteristics of Hydrothermally-altered Andesite in Kalirejo Village and The Surrounding Areas, Indonesia - I Gde Budi Indrawan; Diyan Aditya Putra Pratama; I Wayan Warmada (Geological Engineering Department Universitas Gadjah Mada, 2019)
Type and intensity of hydrothermal alterations affect rock engineering properties and slope stability. Identification of mineralogical characteristics of rocks is essential in determination of rock slope failure mechanism in a hydrothermal alteration zone. This research was conducted to identify mineralogical characteristics of hydrothermallyaltered andesite in Kalirejo Village and surrounding areas, Indonesia. The research was conducted by field observation and laboratory analyses involving petrographic and X-ray Powder Diffraction (XRD) analyses. The results showed that the research area was dominated by argillic alteration type and high alteration intensity implying high susceptibility to slope failures